Bearing capacity and geotechnical properties of sandy soil substrate contaminated with oil derivatives (diesel fuel and kerosene). Issue 4 (2021) - Fazeli, Gholamreza; Lotfollahi, Sina; Bakhtiari, Parham; Farrokhi, Farhang
No abstract available